2014
DOI: 10.4049/jimmunol.1303284
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic TGF-β Signaling Limits Inflammation and Reduces Neuronal Damage during Central Nervous System Toxoplasma Infection

Abstract: The balance between controlling infection and limiting inflammation is particularly precarious in the brain because of its unique vulnerability to the toxic effects of inflammation. Astrocytes have been implicated as key regulators of neuroinflammation in CNS infections, including infection with Toxoplasma gondii, a protozoan parasite that naturally establishes a chronic CNS infection in mice and humans. In CNS toxoplasmosis, astrocytes are critical to controlling parasite growth. They secrete pro-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 62 publications
2
90
0
2
Order By: Relevance
“…For example, in response to IL10, astrocytes release molecules such as TGFβ that promote resolution of inflammation 6163 (Fig. 3 7 ).…”
Section: Astrocyte Anti-inflammatory Mechanismsmentioning
confidence: 99%
“…For example, in response to IL10, astrocytes release molecules such as TGFβ that promote resolution of inflammation 6163 (Fig. 3 7 ).…”
Section: Astrocyte Anti-inflammatory Mechanismsmentioning
confidence: 99%
“…The generation of transgenic mice in which the GFAP promoter was used to drive overexpression of cytokines or alter signaling pathways has highlighted the role of astrocytes in limiting immune infiltration to promote healing (5254). In current models, this extensive gliosis during TE provides a physical barrier to limit tissue damage and isolate areas of pathogen replication (18, 20, 21), but whether astrocytes contribute directly to parasite control in vivo has been difficult to address experimentally. Here, the finding that the GFAP-Cre STAT1 f/f mice fail to control parasite replication in the CNS provides the first in vivo evidence that astrocytes have direct antimicrobial activity that mediates local control of T. gondii .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using mice with lineage-specific deletion of gp130 in astrocytes showed that this cytokine receptor was not intrinsically required for the ability of these cells to control T. gondii but was required to restrict inflammation and prevent astrocyte apoptosis (20). Similarly, the loss of transforming growth factor β (TGF-β) signaling in astrocytes does not affect parasite burden but results in increased CNS inflammation (21). Together, these previous studies emphasize the critical role for astrocytes in limiting CNS inflammation during TE but do not address whether astrocytes have a role in direct parasite control or in promoting local antiparasite responses.…”
Section: Introductionmentioning
confidence: 99%
“…43 Contrary to the proinflammatory role for TGFb1 demonstrated here, TGFb1 signaling in astrocytes limits neuroinflammation in the subacute period after stroke and during toxoplasmic encephalitis. 13,44 In these studies, transgenic mice that expressed a dominant negative type II TGFb receptor in astrocytes were studied. Thus, both Smad and non-Smad downstream signaling pathways would have been inhibited.…”
Section: Discussionmentioning
confidence: 99%